The Role of C-Reactive Protein and Procalcitonin in Infectious Disease Diagnosis - Kareem, Sada Abdullah; Mena Y. Abd; Hammood, Mohammed Neamah; Naser, Maryam Adnan (American Journal of Biology and Natural Sciences, 2025)
C-reactive protein (CRP) and procalcitonin (PCT) are essential biomarkers used in the diagnosis and management of infectious diseases. CRP, an acute-phase protein produced by the liver in response to inflammation, serves as a non-specific marker of infection and tissue injury. Its levels rise rapidly within hours of infection onset and peak within 48 hours, making it useful for detecting bacterial infections, although it lacks specificity in differentiating between bacterial and viral causes. Procalcitonin, a precursor of calcitonin, is more specific for bacterial infections and sepsis. PCT levels increase significantly in response to systemic bacterial infections but remain relatively low in viral infections and non-infectious inflammatory conditions. This specificity makes PCT a valuable tool in guiding antibiotic therapy, reducing unnecessary antibiotic use, and improving antimicrobial stewardship. Both biomarkers play a crucial role in distinguishing bacterial from viral infections, assessing disease severity, and monitoring treatment response. While CRP is widely used due to its cost-effectiveness and availability, PCT provides higher specificity, particularly in identifying severe bacterial infections such as sepsis. Recent studies highlight the combined use of CRP and PCT in clinical practice, enhancing diagnostic accuracy and aiding in early intervention. Despite their advantages, these biomarkers should be interpreted alongside clinical findings and other laboratory parameters to ensure accurate diagnosis and optimal patient management. Further research is needed to refine their clinical applications, particularly in emerging infectious diseases.